2008
DOI: 10.3349/ymj.2008.49.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Korean Version of Obsessive-Compulsive Inventory - Revised in a Non-clinical Sample

Abstract: PurposeThe reliability and validity of a Korean version of the Obsessive-Compulsive-Inventory-Revised (OCI-R) was examined in non-clinical student samples.Materials and MethodsThe Korean version of OCI-R was administered to a total of 228 Korean college students. The Maudsley Obsessive Compulsive Inventory (MOCI), Beck's Depression Inventory (BDI), and Beck's Anxiety Inventory (BAI) were administered to 228 students.ResultsThe total and each of subscale of the Korean OCI-R demonstrated excellent internal consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…Aos doentes com diagnóstico de episódio depressivo major e sem critérios de exclusão -Inventário Depressivo de Beck (BDI), foi utilizado para a avaliação da sintomatologia depressiva (Beck, Steer, & Garbin, 1988). O BDI é utilizado para avaliar a intensidade da depressão ao longo do tempo sobretudo em doentes deprimidos em tratamento (Barkham et al, 2008); para distinguir indivíduos deprimidos dos não-deprimidos em contextos psiquiátricos (Medina, Echeburúa, & Aizpiri, 2007) e outros contextos médicos (Rowan et al, 2005); é igualmente usado para avaliação de sintomas depressivos em populações não clínicas, em estudantes (Gorenstein, Andrade, Zanolo, & Artes, 2005;Lim et al, 2008;O'Connor, Berry, Weiss, & Gilbert, 2002) ou na população geral (Appleton et al, 2008 Scheier, Carver e Bridges (1994). O LOT-R é constituído por 10 itens, dos quais 6 são indicadores de optimismo (itens 1, 3, 4, 7, 9 e 10).…”
Section: Grupo Da População Geralunclassified
“…Aos doentes com diagnóstico de episódio depressivo major e sem critérios de exclusão -Inventário Depressivo de Beck (BDI), foi utilizado para a avaliação da sintomatologia depressiva (Beck, Steer, & Garbin, 1988). O BDI é utilizado para avaliar a intensidade da depressão ao longo do tempo sobretudo em doentes deprimidos em tratamento (Barkham et al, 2008); para distinguir indivíduos deprimidos dos não-deprimidos em contextos psiquiátricos (Medina, Echeburúa, & Aizpiri, 2007) e outros contextos médicos (Rowan et al, 2005); é igualmente usado para avaliação de sintomas depressivos em populações não clínicas, em estudantes (Gorenstein, Andrade, Zanolo, & Artes, 2005;Lim et al, 2008;O'Connor, Berry, Weiss, & Gilbert, 2002) ou na população geral (Appleton et al, 2008 Scheier, Carver e Bridges (1994). O LOT-R é constituído por 10 itens, dos quais 6 são indicadores de optimismo (itens 1, 3, 4, 7, 9 e 10).…”
Section: Grupo Da População Geralunclassified
“…The studies examining the factor structure of the OCI-R replicated the six-factor original structure and it was observed that the discriminant and convergent validity of the OCI-R was excellent (12,13). The psychometric properties of the translated versions (Spanish (14), German (15), French (16), Icelandic (17), Norwegian (18), and Korean) (19,20) were examined. Results of these studies consistently supported the validity of six components of the OCI-R and reported sound psychometric properties for the scale.…”
Section: Introductionmentioning
confidence: 98%
“…The reliability coefficient (α) of ROII-K reported by the original authors was .93, and was .96 in this study. OCI-R-K consists of 18 items rated on 5-point scale, and the reliability coefficient (α) reported by Lim [9] was .90, and was .89 in this study.…”
Section: Measurement Tools and Analysis Methodsmentioning
confidence: 51%
“…ROII-K (Korean version of ROII) translated by Lee [7] in Korean language and validated through Korean people from the Purdon and Clark's original version of ROII (Revised Obsessive Intrusions Inventory) [8] was used to measure obsessional intrusive thoughts experienced by normal people. In order to measure OCD symptoms, OCI-R-K which was translated and tested validity and reliability by Lim [9] from Foa et al's original short version (OCI-R:…”
Section: Measurement Tools and Analysis Methodsmentioning
confidence: 99%